Influence of morphosyntax teaching on reading and writing skills in students of fourth semester from the University of Quindío (2020)
Language has been essential for humans due to the necessity of communication; for that reason, different communities created their own languages and these languages have evolved over time, as well as humans have evolved. Thus, due to this evolution we can find English as the universal language for education, technology, business and industry. In addition, English is increasingly important in Hispanic countries like Colombia, for that reason it has become part of the national education policies. However, in Colombia learning a second language like English can be a headache for most of the students because they are not familiar with the phonetics, structures and functions that are used in this language. According to some experts, Reading and Writing is a complex skill to develop for students because its structure is different from Spanish due to the fact that the first is a Germanic language while the second is a romance language. Nevertheless, the learning of a branch of linguistics such as morphosyntax could influence on Reading and Writing skills because it focuses its study on the internal structure of language, especially the writing part. Thus, in this way students who learn about this branch of linguistics could understand a language like English in a better way.